2012
DOI: 10.1074/jbc.m111.323113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of 14-3-3 Protein-mediated Inhibition of Plant Nitrate Reductase

Abstract: Background: Plant nitrate reductase activity is regulated by phosphorylation and subsequent 14-3-3 protein binding. Results: Steady-state and pre-steady kinetics revealed the electron transfer rates between all three redox-active cofactors and identified the heme-to-molybdenum transfer as key regulatory point. Conclusion: 14-3-3 proteins inhibit domain movement in nitrate reductase. Significance: This is the first description of 14-3-3-regulated electron transfer in a multidomain metallo-enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 38 publications
6
54
0
5
Order By: Relevance
“…Our results rather favor an indirect mechanism by which binding of 14-3-3 dimers causes conformational changes that inhibit SIK catalytic activity. Such structural alterations have been reported for other 14-3-3 ligands including nitrate reductase (NR), RAF proto-oncogene serine/threonine-protein kinase (RAF1), and M-phase inducer phosphatase 2 (CDC25B) [23,40,41]. In case of CDC25B, repression of phosphatase activity is thought to be dependent upon 14-3-3 dimers that form an intramolecular bridge between weak 14-3-3 sites inside the N terminus (S151 or S230) together with the dominant S323 site, blocking cyclin/CDK substrate access as well as impairing access to the nucleus [23,42].…”
Section: Discussionmentioning
confidence: 76%
“…Our results rather favor an indirect mechanism by which binding of 14-3-3 dimers causes conformational changes that inhibit SIK catalytic activity. Such structural alterations have been reported for other 14-3-3 ligands including nitrate reductase (NR), RAF proto-oncogene serine/threonine-protein kinase (RAF1), and M-phase inducer phosphatase 2 (CDC25B) [23,40,41]. In case of CDC25B, repression of phosphatase activity is thought to be dependent upon 14-3-3 dimers that form an intramolecular bridge between weak 14-3-3 sites inside the N terminus (S151 or S230) together with the dominant S323 site, blocking cyclin/CDK substrate access as well as impairing access to the nucleus [23,42].…”
Section: Discussionmentioning
confidence: 76%
“…The NR2 protein binds 14-3-3 through its pSer-534 residue and the 14-3-3 binding results in reduction of its enzymatic activity [63]. We also found that the arginine residues (R) in the 14-3-3 binding site of NR2 were replaced by lysine residues (K), the resulting new motif KKxxpSxP may represent a novel 14-3-3 binding motif.…”
Section: 6mentioning
confidence: 76%
“…Conversely, because acetylation and ubiquitylation compete for Lys residues, antagonistic roles are possible (Danielsen et al, 2011;Wagner et al, 2011). Examples of multiply modified proteins include nitrate reductase, which is ubiquitylated (this article), phosphorylated (Lambeck et al, 2012), and SUMOylated (Park et al, 2011), and the AHA H + -ATPases that are regulated by phosphorylation and possibly ubiquitylation (Palmgren, 2001; this article). Intriguingly, we mapped a site for Ub addition on AHA2 to a strictly conserved Lys (Lys-300) close to the phosphorylation site (Asp-329) that regulates its activity and its potential interaction with the 14-3-3/GRF proteins GRF2 and GRF4 (Baunsgaard et al, 1998), which are themselves likely ubiquitylation targets.…”
Section: Discussionmentioning
confidence: 99%